Pharmacological modulation of prostaglandin E2 (PGE2) EP receptors improves cardiomyocyte function under hyperglycemic conditions. Issue 7 (10th April 2022) - Bosma, Karin J.; Ghosh, Monica; Andrei, Spencer R.; Zhong, Lin; Dunn, Jennifer C.; Ricciardi, Valerie F.; Burkett, Juliann B.; Hatzopoulos, Antonis K.; Damron, Derek S.; Gannon, Maureen
Abstract: Type 2 diabetes (T2D) affects >30 million Americans and nearly 70% of individuals with T2D will die from cardiovascular disease (CVD). Circulating levels of the inflammatory signaling lipid, prostaglandin E2 (PGE2 ), are elevated in the setting of obesity and T2D and are associated with decreased cardiac function. The EP3 and EP4 PGE2 receptors have opposing actions in several tissues, including the heart: overexpression of EP3 in cardiomyocytes impairs function, while EP4 overexpression improves function. Here we performed complementary studies in vitro with isolated cardiomyocytes and in vivo using db/db mice, a model of T2D, to analyze the effects of EP3 inhibition or EP4 activation on cardiac function. Using echocardiography, we found that 2 weeks of systemic treatment of db/db mice with 20 mg/kg of EP3 antagonist, beginning at 6 weeks of age, improves ejection fraction and fractional shortening (with no effect on heart rate). We further show that either EP3 blockade or EP4 activation enhances contractility and calcium cycling in isolated mouse cardiomyocytes cultured in both normal and high glucose. Thus, peak [Ca 2+ ]I transient amplitude was increased, while time to peak [Ca 2+ ]I and [Ca 2+ ]I decay were decreased. These data suggest that modulation of EP3 and EP4 activity has beneficial effects on cardiomyocyte contractility and overall heart function. Abstract : Circulating levels of PGE2 are elevated in obesity and T2D and are associated with decreased cardiac function. The EP3 and EP4 PGE2 receptors have opposing actions in the heart: overexpression of EP3 in cardiomyocytes impairs function, while EP4 overexpression improves function. We show that treatment of T2D mice or cardiomyocytes cultured in high glucose with a PGE2 receptor modulators improves cardiac contractility and calcium cycling in mouse cardiomyocytes cultured in high glucose.